BRST invariant scalar and vector operators in the SU(2) × U(1) Higgs model - Dudal, D.; van Egmond, D. M. [UNESP]; Peruzzo, G.; Sorella, S. P. (Springer Nature, 2023)
We present a set of BRST invariant composite operators in the SU(2) × U(1) Higgs model which exhibit an overlap with the observable scalar and vector particle states of the theory. Some of these operators are non-local in the standard formulation of the Higgs model, however, we show that they can be localized using the Stuckelberg trick, this without changing the physical content. These operators provide thus a BRST invariant resolution of the physical spectrum of the theory, thereby giving the next step in constructing a manifestly BRST invariant formulation of the particle spectrum of the Electroweak and Standard model.
Keywords: Composite operators; Higgs model; Invariant formulation; Localised; Nonlocal; Particle spectrum; Particle state; Spectra's; Vector operators; Vector particles